Orientation and Mobility Assessments for Children and Youths With Visual Impairments: How, Why, When, and Where?. (September 2022) - Kaiser, Justin T.; Herzberg, Tina S.
Introduction: This study analyzed survey responses from 114 orientation and mobility (O&M) specialists regarding the content and procedures they used in completing O&M assessments.Methods: O&M specialists completed an online survey in 2020 on their assessment practices for children and youths who are visually impaired.Results: Over 85% of participants identified that they interview the student, parent, classroom teacher, and teacher of students with visual impairments as part of the assessment. The only visual skills addressed by at least 80% of participants were depth perception, distance acuity, scanning, and peripheral visual fields. Students without additional disabilities in kindergarten through 12th grade were more likely to be taught the two-point touch cane technique when compared to students with additional disabilities, who were more likely to be taught constant contact.Discussion: Participants identified that O&M assessments for students in 9th–12th grade were more likely to focus on skills that would be needed for employment or post-secondary education or both, such as the use of public transportation. For students with additional disabilities or children under the age of five years, participants were more likely to conduct assessments focused on safety and immediate needs and environments.Implications for Practitioners: Appropriate O&M assessments need to be conducted in natural environments that provide equal challenges to the environments where students need to travel. O&M specialists must adapt the assessment content and procedures to address the current and future travel needs of all students with visual impairments.